Employment and Unemployment Trends in the Baltic Countries and Statistical Regions of Latvia, 1998–2011 - Ulnicāns, Einārs (Lithuanian Journal of Statistics, 2011)
The aim of the paper is to analyse the number and proportion of employees, unemployment rates and theirterritorial trends in Latvia, and to compare them with those in Estonia and Lithuania. The paper analyses the number ofemployees at the main job, its proportion in the private sector, and unemployment rates in the Baltic countries and statisticalregions of Latvia. In 2000–2007, employment and its proportion in the private sector was on the increase. In 2008, an upwardtrend in Estonia and Lithuania started to decrease, but in Latvia number of employees and its proportion in the private sectoralready had dropped. In 2009, the number of employees continued to decline. The unemployment rate grew from 1998 to2000 and from III quarter 2008 to I quarter 2010. From 2001 to II quarter 2008, during an economic boom, it decreased to aminimum. A faster economic growth means a higher proportion of employees in the private sector; however, during theeconomic crisis, it creates more instability in the labour market than in the public sector, especially at the beginning. As thecrisis deepens, unemployment in the private sector begins to stabilize; however, it increases in the public sector.
Keywords: employees at the main job; proportion of employees in the private sector; unemployment rate; Baltic countries; statistical regions of Latvia